Lower body positive pressure running: A tool for early return to sport? - Cabri, J.; Nicol, C.; Ishikawa, M.; Chavet, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Several studies have investigated the effects of reducing gravity on locomotion kinematics and kinetics. Lower body positive pressure (LBPP) treadmill allows running in partial unweighing conditions and is proposed as a tool for early return to sport. This invited symposium focuses on the influence of short term unweighing on running patterns. Quantifying the pre- and post-impact phase lower limb muscle activities and muscle-tendon loading in healthy as well as in patients 6 months after ACL reconstruction, it provides a multi-scale screening of partial unweighing effects on locomotor patterns. The first presentation entitled "Neural and kinetic adjustments in short-term unweighing running" deals with the unweighing and reloading induced-changes in the vertical ground reaction forces and of the activity of major lower limb muscles. Special emphasis is put on the timing of neuromechanical changes. Short-term unweighing and reloading are found to result in mirrored changes. The unweighing phase shows increased flight time with unchanged contact time. In the absence of modification of the triceps surae EMG during preactivation and braking, the observed overall decrease in vertical ground reaction forces is attributed to the vertical support provided by the anti-gravity treadmill chamber. The increased EMG stability with body weight reduction is considered as a protective mechanism facing such unusual loading condition. This limits the expected improvement in running economy, but favors the readjustments to normal body weight condition. The after-effects highlight the fact that 3 min of unweighing are sufficient for an updating of the running pattern. The second presentation focuses on "the short-term influence of unweighing on muscle fascicle and tendon loading" in standing, hopping and running conditions. As similar to the intensity and movement specific muscle fascicle regulation, unweighing and reloading conditions can modify muscle fascicle length not only in standing but also in movement conditions. However, it is not clear how our neuromuscular system is regulated under unweighing and reloading conditions. This presentation highlights muscle-tendon interactions together with the neural adjustments during human movements under unweighing and reloading conditions. The third presentation is dealing with "the use of unweighing running to detect proprioceptive functional impairments". ACL ligamentoplasty leads to long lasting proprioceptive and functional deficits. In rehabilitation, LBPP treadmill running is considered allowing earlier return to practice. Our own running protocol performed 6 months post ACL reconstruction revealed increased interlimb asymmetry in temporal dynamics and muscle activity while running in unweighing conditions. This highlights the interest of such protocol for detecting remaining locomotor impairments.